2016
DOI: 10.3892/ol.2016.4207
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SOX2 in oral squamous cell carcinoma and the association with lymph node metastasis

Abstract: Abstract. Oral squamous cell carcinomas (OSCCs) are a growing problem in the world. The various existing treatments have not markedly improved the survival rate of patients with OSCC during the past three decades. Novel treatment strategies are required. Sex determining region Y-box 2 (SOX2) is a transcription factor that is involved in the maintenance of embryonic stem cell pluripotency and in multiple developmental processes. SOX2 expression was indicated to act as a prognostic factor in various types of tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 98 publications
3
46
0
1
Order By: Relevance
“…Accordingly, decreased expression of SOX2 is significantly associated with decreased angiogenesis and lymphangiogenesis in breast cancer (Chen et al, 2008). Another study on lung cancer indicated the association of SOX2 with lymphatic metastasis (Ren et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Accordingly, decreased expression of SOX2 is significantly associated with decreased angiogenesis and lymphangiogenesis in breast cancer (Chen et al, 2008). Another study on lung cancer indicated the association of SOX2 with lymphatic metastasis (Ren et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…A significant association has been reported between the expression of OCT4, SOX2, and NANOG with the grade of OSCC (Chiou et al, 2008;Vaiphei et al, 2014). OCT4, SOX2 and NANOG are the key transcription factors involved in pluripotency of embryonic stem cells and also regulating the fate of stem cells (Li et al, 2015;Nichols et al, 1998;Ren et al, 2016). Their expression decrease during cells differentiation (Fu et al, 2016;Islam et al, 2015;Ren et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OSCC is the most usual oral tumour, which is prone to metastasis to lymph nodes [22]. The classical treatments have been unable to achieve a satisfactory therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic alterations, such as the change of gene expressions of tumor suppressor genes and oncogenes, also play important roles in the development of OSCC [5]. A few review articles [6][7][8][9] summarized genetic anomalies associated with OSCC according to the type of structure affected (chromosome, allele, oncogene, tumor suppressor gene, or nucleotide) and the type of anomaly (polymorphism, point mutation, deletion, and other alterations). Many OSCC-associated genes (e.g., TP53, CDKN2A, Cyclin D1, EGFR, SMAD-2, SMAD-4, CDK2AP1, FHIT) have been identified [4,7,8,10].…”
Section: Introductionmentioning
confidence: 99%